In vitro morphogenetic responses and cytokinin-auxin interaction for callus production in pepper - BARROSO , MARÍA LUISA; RUBLUO , ABRAHAM (Anales del Instituto de Biología serie Botánica, 2009)
MERISTEMS OF TWO CAPSICUM SPECIES WERE CULTURED IN MS MEDIUM SUPPLEMENTED WITH SVERAL CYTOKININ AND AUXIN COMBINATIONS. EFFICIENCIES IN BUD AND SHOOT PRODUCTION WERE DIFFERENT IN BOTH SPECIES. THE BEST RESPONSE IN C CHINENSE WAS ATTAINED WITH A BA (2.0MG/L) IAA (1.0 MG/L) COMBINATION, WHILE IN C. ANNUUM IT OCCURRED WITH K (2.0 MG/L) IAA (1.0 MG/L). HYPOCOTYL SECTIONS OF C ANUUM WERE ALSO CULTURED. THE MORPHOGENETIC RESPONSE OF THIS EXPLANT WAS POOR, EVEN THOUGH ABUNDANT CALLUS WAS ACHIEVED. FRESH AND DRY WEIGHT WERE EVALUATED. AN EXPONENTIAL RESPONSE WAS OBSERVED WITH THE MAXIMUM MULTIPLICATION RATE OF CALLUS AFTER TWO MONTHS UNDER CULTURE; K (2.0 MG/L) 2.4-D (1.0 MG/L) COMBINATIONS RENDERED THE BEST CALLUS PRODUCTION.